The application of quality control circle in improving the accuracy of ICD coding on medical records - Wenjing Ou; Peiyan Chang; Jinghua Zhou; Zhiqiang Zhou; Mingfang Jiang; Chao Wu (BMC Health Services Research)
Abstract Objective This study aims to explore effective methods for reducing the International Classification of Diseases (ICD) coding error rate on the first page of inpatient cases using Quality Control Circle (QCC) management tools. The goal is to enhance the quality of data on the initial page of cases and elevate the competency of coders. Methods A total of 4,613 medical case front pages from patients discharged between March 1, 2024, and March 31, 2024, were selected as the pre-QCC intervention group. Additionally, 4,489 inpatient case front pages from discharges occurring between July 1, 2024, and July 31, 2024, were designated as the post-QCC intervention group. The QCC team was established within the Department of Case Management, focusing on the theme: “Improving the Accuracy of ICD Coding on Medical Case Front Pages.” Guided by the Plan-Do-Check-Act (PDCA) cycle framework, the team implemented QCC activities following its ten-step methodology. Both tangible outcomes (e.g., coding error rates) and intangible outcomes (e.g., staff skill enhancement) were evaluated before and after the intervention. Results A follow-up examination of the coding on the first page of 4,489 inpatient cases discharged in July 2024 revealed a significant reduction in the overall error rate, from 7.02% before the intervention to 2.90% afterward (χ²=81.791, P < 0.001). Specifically, the error rate for primary diagnoses decreased from 1.86 to 0.65% (χ²=27.067, P < 0.001), other diagnoses from 2.88 to 1.54% (χ²=18.996, P < 0.001), surgical operations from 1.99 to 0.71% (χ²=27.804, P < 0.001), and pathologic diagnosis error rates dropped from 0.17 to 0% (P = 0.008). Additionally, the coding error rate for external causes of injury and poisoning fell from 0.11 to 0% (P = 0.033). The goal achievement rate reached 111.6%, with a progress rate of 58.68%. Among the intangible achievements, participants demonstrated notable improvements in problem-solving, communication, quality control methodologies, and innovation skills. Conclusion The application of QCC tools not only significantly enhances the accuracy rate of ICD coding in inpatient medical records but also improves coders’ problem-solving capabilities and communication skills. Consequently, it facilitates continuous quality improvement in the coding of inpatient medical record front pages, thereby promoting sustained advancement in healthcare data management standards.